2022
DOI: 10.1038/s41419-022-04719-7
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 critically mediates TMAO-induced inflammatory response in vascular smooth muscle cells

Abstract: A high plasma level of the choline-derived metabolite trimethylamine N-oxide (TMAO) is closely related to the development of cardiovascular disease. However, the underlying mechanism remains unclear. In the present study, we demonstrated that a positive correlation of protein arginine methyltransferase 5 (PRMT5) expression and TMAO-induced vascular inflammation, with upregulated vascular cell adhesion molecule-1 (VCAM-1) expression in primary rat and human vascular smooth muscle cells (VSMC) in vitro. Knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…PTX-Mediated Upregulation of PRMT5 Requires Increased NOX4 in DRG Neurons NOX4 contributes to PRMT5 expression in inflammatory disease. 18 Due to the fact that PTX can also affect NOX4 expression, 13 as well as the fact that the abovementioned results demonstrated that PRMT5 in the DRG modulates the progression of PTX-induced neuropathic pain, we further proposed that PTX-mediated upregulation of PRMT5 may require increased NOX4. Western blot analysis demonstrated that PTX increased the abundance of NOX4 in DRGs at days 7, 14, and 21 after treatment (Figure 3A).…”
Section: Ptx-induced Neuropathic Pain Is Reversed By the Prmt5 Inhibi...mentioning
confidence: 87%
“…PTX-Mediated Upregulation of PRMT5 Requires Increased NOX4 in DRG Neurons NOX4 contributes to PRMT5 expression in inflammatory disease. 18 Due to the fact that PTX can also affect NOX4 expression, 13 as well as the fact that the abovementioned results demonstrated that PRMT5 in the DRG modulates the progression of PTX-induced neuropathic pain, we further proposed that PTX-mediated upregulation of PRMT5 may require increased NOX4. Western blot analysis demonstrated that PTX increased the abundance of NOX4 in DRGs at days 7, 14, and 21 after treatment (Figure 3A).…”
Section: Ptx-induced Neuropathic Pain Is Reversed By the Prmt5 Inhibi...mentioning
confidence: 87%
“… 18 , 35 Lactobacillus is also positively associated with trimethylamine N ‐oxide (TMAO) levels. 36 The TMAO has been associated with the risk of CVDs such as vascular inflammation, 37 atherosclerosis, and heart failure. 38 Moreover, TMAO promotes angiotensin II‐induced vasoconstriction and aggravates angiotensin II‐induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of this study demonstrated that oxidative stress activation is required for TMAO-induced inflammation, and it involves molecular mechanisms, such as the suppression of the AMPK/SIRT1 signaling pathway [ 120 ]. In an in vitro study, TMAO induced the inflammatory reaction and the synthesis of ROS and favored the expression of adhesion molecules in vascular smooth muscle cells via nicotinamide adenine dinucleotide phosphate oxidase 4 (Nox4)/protein arginine methyltransferase 5 (PRMT5)/NF-κB p65/VCAM-1 signaling cascade [ 121 ]. Supplementary studies showed that TMAO could stimulate MAPK/ERK/NF-κB cascade [ 122 ] and NLRP3 activation through the SORT3-SOD2-mitochondrial ROS signaling pathway [ 123 ] to promote vascular inflammation as an atherogenic condition.…”
Section: Gut Molecules and Cardiovascular Diseasesmentioning
confidence: 99%